2010
DOI: 10.1016/j.adolescence.2009.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in adolescent career preparation: Social support, personality and the development of choice decidedness and congruence

Abstract: This longitudinal panel study investigated predictors and outcomes of active engagement in career preparation among 349 Swiss adolescents from the beginning to the end of eighth grade. Latent variable structural equation modeling was applied. The results showed that engagement in terms of self‐ and environmental‐exploration and active career planning related positively to interindividual increases in career decidedness and choice congruence. More perceived social support, early goal decidedness, and particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
2
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 43 publications
(45 reference statements)
4
72
2
14
Order By: Relevance
“…Moreover, career management skills can be used to capitalize on one resource to develop another, for example, when focused environmental career exploration, capitalizing on identity resources in terms of goal and preference clarity, builds human capital resources in terms of career knowledge. The positive relationships of components within the four resources are indicated in numerous empirical studies in the career literature (e.g., Hirschi, Niles, & Akos, 2011).…”
Section: The Relationship Between the Four Career Resourcesmentioning
confidence: 99%
“…Moreover, career management skills can be used to capitalize on one resource to develop another, for example, when focused environmental career exploration, capitalizing on identity resources in terms of goal and preference clarity, builds human capital resources in terms of career knowledge. The positive relationships of components within the four resources are indicated in numerous empirical studies in the career literature (e.g., Hirschi, Niles, & Akos, 2011).…”
Section: The Relationship Between the Four Career Resourcesmentioning
confidence: 99%
“…We applied the German-language adaptation of the vocational identity scale (Holland, Daiger, & Power, 1980;Jörin, Stoll, Bergmann, & Eder, 2004) using seven items (e.g., "I"m not sure yet which occupations I could perform successfully"). Research with the German-language version reported scale reliabilities between α = .81 and .89 and showed that the scale correlated highly with other measures of career decidedness, moderately with career planning, and low with career exploration among adolescents and college students (Hirschi, Niles, & Akos, 2011;Jörin Fux, 2006).…”
Section: Calling and Career Preparation 12mentioning
confidence: 99%
“…Para o intervalo relativo ao período de estágio, as correlações entre os valores médios obtidos em cada um dos momentos (T1xT2) sugerem alguma estabilidade na atividade exploratória e nos níveis de indecisão, de compromisso e de autoefi cácia. Na verdade, a literatura aponta o resultado apresentando em T1 como o melhor preditor de cada uma destas variáveis em T2 (e.g., Carless & Prodan, 2003;Hirschi et al, 2011;Kracke & Schmitt-Rodermund, 2001;Lent et al, 1994;Patton & Creed, 2001;Rogers & Creed, 2011) sobretudo quando nos aproximamos do fi m da adolescência e assistimos a alguma estabilização dos processos vocacionais mais diretamente envolvidos na tomada de decisão e compromisso de carreira (Harren, 1979;Porfeli & Lee, 2012;Skorikov, 2007;Super et al, 1996). No entanto, se globalmente a experiência de estágio tem impacto no desenvolvimento vocacional dos alunos, tal como é colocada, esta relação não responde à nossa principal questão -quais as qualidades do estágio que melhor explicam as mudanças ocorridas.…”
Section: Discussão Dos Resultadosunclassified
“…A literatura sugere, de forma consistente, que o suporte proporcionado no contexto de trabalho permite reduzir a ansiedade e o stresse experimentado neste tipo de situações, estimula a procura de apoio, aumenta a confi ança na realização de novas tarefas e facilita a partilha de experiências (e.g., Blustein et al, 1995;Hirschi, 2009;Hirschi, Niles, & Akos, 2011;Kenny & Bledsoe, 2005), sendo que neste contexto deve ser destacado o papel do supervisor e dos professores orientadores (e.g., Cheung & Arnold, 2010;Creed, Fallon, & Hood, 2009;Kenny & Bledsoe, 2005). Juntamento com o suporte, os contextos devem ser desafi antes, promover a autonomia, apresentar um grau de estruturação adequado e permitir a aquisição de novas competências (Ryan & Deci, 2000).…”
Section: Qualidade Da Experiência De Estágio E O Processo De Exploraçunclassified